PLC and HMI Based Control and Monitoring System of the Xeno Drinking Water Factory - southisombath, phouvithath; thongphanh, phoudsavann (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The automation of small-scale production facilities using affordable technology is critical for enhancing operational efficiency in developing regions. Previously, the Xeno Drinking Water Factory, located in Savannakhet Province, Lao PDR, faced significant challenges, including inaccurate manual bottle counting, inefficient water tank level monitoring, and the absence of reliable production data. This study presents the design and implementation of an automated bottling system based on a Programmable Logic Controller (PLC) and a Human-Machine Interface (HMI) for 20-liter drinking water bottles. The developed system integrates a Mitsubishi FX1N-40MR PLC, a SAMKOON HMI, and a proximity sensor to automate bottle counting and system status display. Comprehensive testing demonstrated that the system achieved 100% accuracy in bottle counting, provided real-time alerts, and supported both manual and automatic operation modes. As a result, labor requirements were reduced from three workers to two, and the average bottling time per bottle decreased from 40.2 seconds to 36.5 seconds. Moreover, the reliability of production data improved from a previously high manual error rate to 0%, enabling more effective management and decision-making. This low-cost, scalable automation solution offers a practical model for similar small and medium-sized manufacturing enterprises in developing regions seeking to improve efficiency and data accuracy.